The effect of professional certification, professional commitment, and professionalism on lecturer's performance - Maimunah, Mutiara; Lesmana, Desy; Panjaitan, Delfi (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
This research aims to analyze and determine the effect of professional certification, professional commitment, and professionalism on lecturer performance. This type of research is quantitative research. The population in this research were accounting lecturers at 12 private universities (PTS) in the city of Palembang. The data collection technique used a survey technique by distributing 85 questionnaires to accounting lecturers at private universities who have accounting profession certification, containing a list of questions to respondents directly and the data analysis technique used was multiple regression analysis technique. The results showed that professional certification, professional commitment, and professionalism had a positive effect on lecturer performance.